THE INFLUENCE OF Pb (II) ION CONCENTRATION ON PROTEIN CONTENT IN MUSSEL SHELLS (Mactra violacea) IN CONTAMINATED AREA OF TARAKAN ISLAND EAST KALIMANTAN - Tanjung, Faisal; Kartika, Rudi; Hindryawati, Noor (JURNAL ATOMIK, 2018)
The researched about the correlation level of metal lead (Pb) towards the protein content of mussel shells (Mactra violacea) had been done. This research was taken in the coastal water of Tarakan, North Borneo. The research aimed to know concentration of ion (Pb) and protein content of mussel shells (Mactra violacea) based on the size and location of the different sampling. Afterwards, the lead (Pb) metal and protein were correlated using Least Square method. Analysis of concentration of Pb ion was performed by using AAS (Atomic Absorption Spectrofotometry) and analysis of protein content using Kjehdal method. From this research, it was found the concentration of Pb ion on point 1 is by an average of 0.7220 mg/L, on point 2 is by an average of 0.7433 mg/L and point 3 is by an average of 0.9208 mg/L. It is also found the content protein of mussel shells (Mactra violacea) on point 1 is by an average of 19,9883%, on point 2 it was found the average of protein content of 21.7714% and point 3 by an average 22.8664%. The correlation concentration of Ion Pb towards protein conten on kerang kepah (Mactra violacea) symbolized as r = 0.8448.